Clinical trials in allergen immunotherapy: current concepts and future needs. Issue 9 (16th April 2018) - Pfaar, O.; Alvaro, M.; Cardona, V.; Hamelmann, E.; Mösges, R.; Kleine‐Tebbe, J.
Abstract: Allergen immunotherapy (AIT) is a safe, effective treatment for allergic rhinoconjunctivitis and allergic asthma. However, AIT's clinical effect is still contested—primarily due to heterogeneity in clinical trial designs, study populations, therapeutic formulations, and efficacy criteria. After discussing current concepts and unmet needs, an international panel of experts made several recommendations: (i) explore and validate definitions for (clinical) responders in AIT trials; (ii) use of well‐documented, standardized provocation tests prior to inclusion of subjects with relevant diseases in AIT trials; (iii) monitoring neo‐sensitizations and occurrence of new allergy in extended AIT trials, and exclusion of polyallergic participants; (iv) validation of allergen exposure chambers with regard to natural exposure; (v) in studies of seasonal allergies, focus on peak exposure but also consider organizing two parallel, geographically distinct but otherwise identical trials; (vi) discuss adaptive trial designs with the regulatory authorities; (vii) use e‐health and m‐health technologies to capture more information on individual exposure to allergens; (viii) initiate research on potential psychological, biochemical, immune, neural, and even genomic markers of the placebo response; (ix) identify trial designs and primary endpoints that will give children with allergies easier, faster access to AIT formulations; and (x) promote and apply standardized methods for reporting systemic and local adverse events. The latest technologies and trial designs may provide novel, ethical ways of reducing bias and heterogeneity in AIT clinical trials. There is scope for physicians, patient organizations, companies, and regulators to improve clinical trials in AIT and, ultimately, to provide patients with better treatments.